Hubungan antara intensitas penggunaan Aplikasi TikTok dengan self-control remaja - Iis Farida Aryani; Galih Fajar Fadillah; Angga Eka Yuda Wibawa (Journal of Psychology and Treatment, 2026)
TikTok has become one of the most popular social media platforms among adolescents and may be associated with their level of self-control. This study aimed to examine the relationship between the intensity of TikTok use and self-control among members of youth organization in Klarisan Village, Ampel District. The study employed a quantitative approach with a correlational design. The population comprised 110 adolescents, and 86 respondents were selected through purposive sampling. Data were collected through observation and a Likert-scale questionnaire. The research instruments were tested for validity and reliability. The Kolmogorov-Smirnov test was used to assess data normality, and Pearson's Product-Moment Correlation was used to test the hypothesis. The findings revealed a positive and significant relationship between the intensity of TikTok use and adolescents’ self-control. This indicates that higher levels of TikTok use were associated with greater self-control. These findings suggest that TikTok use is not necessarily associated with poor self-control. Therefore, family and community guidance is needed to promote healthy, purposeful, and responsible social media use.